Cascade domino lithography for extreme photon squeezing. (October 2020) - Kim, Inki; Mun, Jungho; Baek, Kwang Min; Kim, Minkyung; Hao, Chenglong; Qiu, Cheng-Wei; Jung, Yeon Sik; Rho, Junsuk
Graphical abstract: Abstract: Squeezing photons into deep sub-wavelength volumes and few-nanometer gaps has led to the investigation of interesting phenomena, including strong coupling, quantum plasmonics, nonlinearity enhancement, nonlocality, and molecular junctions. The common configuration of bowtie nanoantennas has been extensively studied owing to the great enhancement of the localized electromagnetic field. The enhancement rapidly increases as the tips become sharper and the gap becomes narrower. However, reliable fabrication of nanoantennas that are extremely sharp with sub-10 nm gaps is statistically prohibited due to the fundamental limitation of the proximity effect of electron beam lithography. Here, an intuitive "fall-to-rise" scheme is proposed and experimentally validated using a new concept of cascade domino lithography. In this report, we successfully establish a controllable lithography method of making extremely sharp bowtie nanoantennas with sub-1 nm radius of curvature reaching the size of a gold nanocluster as well as single-digit-nanometer gaps between such sharp tips. In addition, a proof-of-concept application of surface enhanced Raman spectroscopy is demonstrated along with rigorous full-wave electromagnetic simulations and numerical analysis. This control of falling nanostructures opens up an unexplored gateway towards conquering the limitations of experimentally exploring the realm of plasmonics down to the sub-nanometer regime.